Evaluación de la crioconservación de embriones bovinos (Bos taurus) por dos métodos de descenso de temperatura en el laboratorio de biotecnología de la reproducción de la carrera de medicina veterinaria de la Universidad Técnica de Cotopaxi - García Gallardo, Myriam Verónica (2014)
Cryoconservation is considered the technique of choice for bovine embryos produced “in vivo”. During the freezing process, embryonic cells undergo significant changes associated with the formation of intra-or extracellular ice that may decrease the survival pos cryoconservation. To minimize these problems, it resort to use of "cryo protective substances"; as well as a temperature decrease rates controlled by the use of programmable freezers machines that are very expensive. Nowadays no freezing or vitrification protocol available ensures the overall integrity of the structures preserved in this way. According Dobrinsky, it is not important "as" the embryos are cryoconserved,” always someone dies....